The Routine Determination of the Endogenous Thrombin Potential, First Results in Different Forms of Hyper- and Hypocoagulability - Wielders, Simone; Mukherjee, Manjari; Michiels, Jan; Rijkers, Dirk T S; Cambus, Jean-Pierre; Knebel, Richard W C; Kakkar, Vijay; Hemker, H Coenraad; Béguin, Suzette (Thrombosis and Haemostasis, 1997)
The area under the thrombin generation curve (the endogenous thrombin potential; ETP) has been proposed as a parameter for plasma-based hypercoagulability and to monitor anticoagulant treatment. We present an ETP assay for the routine laboratory using a centrifugal analyser. Throughput is 30 samples/h, within and between run imprecision is 4-5.6%. Suitable substrates were developed for the ranges of 10-500% and 2-100% of normal.Independent of tissue factor concentration (if >4 pM), the normal value of the extrinsic ETP is 384.8 ±51.7 nM.min. The intrinsic ETP, triggered by ellagic acid, is 414 ± 41 nM.min.The ETP is decreased to 15 and 35% of normal by oral anticoagulation (INR 2.5-4.0) and by heparin administration (APTT 1.5-2.5 X control).The ETP is increased in untreated subjects with congenital antithrombin deficiency and in women using oral contraceptives. In deep vein thrombosis (phlebographically confirmed), it is increased by 29.4% (extrinsic) and 53% (intrinsic). In (angiographically assessed) coronary artery disease the increase is by 10% and 17% respectively.